(untitled) (Research, Society and Development, 2023)
The objective of this study is to evaluate the amount of sodium present in these beverages, considering the nutritional recommendations of health organizations for the prevention of chronic non-communicable diseases. Exploratory research, based on the evaluation of 14 brands of UHT protein dairy beverages and their flavor variations, totaling 61 products. The information was collected from the nutritional tables on each product’s labels at various distribution points for a standardized 250ml portion. Compliance with current legislation regarding the presentation of sodium values on labels was observed, with a variation of up to 325.4% in sodium levels between samples. There was no correlation between the recommended daily reference values for energy and sodium between the samples, making it difficult to truly perceive the potential health risk associated with excessive consumption of sodium present in these foods. In this sense, the methodology of the Nutritional Profile Model of the Pan American Health Organization - MPN/OPAS proves to be promising for improving the labeling of UHT protein dairy beverages, as it better highlights the sodium contribution of the food to the diet. total and facilitates the exercise of critical behavior and conscious food choices. This study becomes a pioneer in the analysis of the possible impacts of the sodium content of UHT protein dairy beverages on health. Therefore, it is recommended that further work on these products be carried out, with the aim of not only evaluating sodium levels, but also other critical nutrients in disease prevention and health promotion.